2021
DOI: 10.1186/s12981-021-00352-0
|View full text |Cite
|
Sign up to set email alerts
|

Virologic outcomes of switching to dolutegravir functional mono- or dual therapy with a non-cytosine nucleoside analog: a retrospective study of treatment-experienced, patients living with HIV

Abstract: Background Dolutegravir (DTG) monotherapy results in virologic failure and the development of DTG resistance. Here, we evaluated virologic outcomes of patients switched to DTG functional mono- or dual therapy with a non-cytosine nucleoside analog (NA). Methods This retrospective, single center study included treatment-experienced patients switched to regimens containing ≥ 2 antiretrovirals between 8/13/13–11/22/14 who were later found to be on DTG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…The strong associations of DTG resistance with DTG monotherapy and NRTI resistance are consistent with previous findings, 10,31,32 but appear to contradict the results from the NADIA trial, which found no evidence that the efficacy of DTG-based ART is affected by resistance to the NRTI backbone.…”
Section: Discussionsupporting
confidence: 81%
“…The strong associations of DTG resistance with DTG monotherapy and NRTI resistance are consistent with previous findings, 10,31,32 but appear to contradict the results from the NADIA trial, which found no evidence that the efficacy of DTG-based ART is affected by resistance to the NRTI backbone.…”
Section: Discussionsupporting
confidence: 81%
“…The risk factors associated with DTG-m virological failure (VL) may well apply to dual therapies including dolutegravir plus a second antiretroviral with low genetic barrier to resistance. This concern of “functional dolutegravir monotherapy” is particularly relevant in the context of previous treatment failure with resistance [ 1 , 13–16 , 27 ]. Finally, potential metabolic problems may arise when DTG is combined with tenofovir alafenamide [ 28 , 29 ].…”
mentioning
confidence: 99%
“…Using this approach to exclude defective genomes resulted in improved specificity and agreement with previously or concurrently detected mutations in the blood plasma [24,25]. Taken together, the low reproducibility of currently available archived drug resistance testing, the low proportion of intact proviruses in patients who are virologically suppressed and the high success rate of high genetic barrier regimens, such as ritonavir-boosted protease inhibitor-based or dolutegravir-based regimens, even in cases of functional monotherapy [26–28] may explain the limited value of archived drug resistance in predicting or improving clinical outcomes.…”
Section: Assessing Hiv Drug Resistance In Blood Cellsmentioning
confidence: 87%